Solar sail technology—A state of the art review. (October 2016) - Fu, Bo; Sperber, Evan; Eke, Fidelis
Abstract: In this paper, the current state of the art of solar sail technology is reviewed. Solar sail research is quite broad and multi-disciplinary; this paper focuses mainly on areas such as solar sail dynamics, attitude control, design and deployment, and mission and trajectory analysis. Special attention is given to solar radiation pressure force modeling and attitude dynamics. Some basics of solar sailing which would be very useful for a new investigator in the area are also presented. Technological difficulties and current challenges in solar sail system design are identified, and possible ideas for future research in the field are also discussed.